"A Study on India’s New Education Policy in Science Education: Aligning Curriculum with Sustainability Goals" (International Journal of Food and Nutritional Sciences, 2023)
This research looks at how sustainability education is brought into the scientific curricula of Indian higher education institutions given the New Education Policy (NEP). It will evaluate quantitative and qualitative aspects aligned with Sustainable Development Goals (SDG) on how it is being implemented now and how matched it is. The research builds on secondary data from one source and from several others, illustrating a problematic implementation gap—that many universities offer environmental science courses but few or none on sustainability science courses. However, there is a need for targeted policy interventions because statistical studies show that government colleges teach environmental education more than private colleges. Secondly, this SDG alignment study also highlights that a fully developed curriculum is essential for the raising of environmentally informed citizens. The results indicate that sustainability education needs to be taught in all the higher education in India to equip graduates adequately to handle India’s urgent sustainability challenges.